2023
DOI: 10.1002/hup.2862
|View full text |Cite
|
Sign up to set email alerts
|

Dexamphetamine influences funneling illusion based on psychometric score

Abstract: Objectives Our team previously showed that like the experience of the rubber hand illusion (RHI) in people with schizophrenia and their offspring¸ dexamphetamine administration to healthy volunteers increases the stimulus binding windows (BWs) in RHI. It is not clear if similar expansions of BWs are present for unimodal illusions. Studies have also shown that subjective or objective effects of amphetamine would be linked to between‐person variations in personality measures. Therefore, we aimed to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 106 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…As shown in Fig 4 , wilcoxon signed rank test with continuity correction indicated that there was a significant increase in PLE scores following d-amphetamine (V = 199, p = 0.00048), relative to placebo (presented in our previous report on funneling illusion [ 100 ]). As shown in Table 1 , d-amphetamine significantly increased scores on the BPRS (V = 129, p = 0.001), MIS (V = 107.5, p = 0.039) and PAS (V = 127, p = 0.017), but not on the Launay-Slade (V = 75, p = 0.16) or SAPS (V = 124.5, p = 0.092) Out of the total of 20 participants, d-amphetamine increased schizotypy scores in 16 participants.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…As shown in Fig 4 , wilcoxon signed rank test with continuity correction indicated that there was a significant increase in PLE scores following d-amphetamine (V = 199, p = 0.00048), relative to placebo (presented in our previous report on funneling illusion [ 100 ]). As shown in Table 1 , d-amphetamine significantly increased scores on the BPRS (V = 129, p = 0.001), MIS (V = 107.5, p = 0.039) and PAS (V = 127, p = 0.017), but not on the Launay-Slade (V = 75, p = 0.16) or SAPS (V = 124.5, p = 0.092) Out of the total of 20 participants, d-amphetamine increased schizotypy scores in 16 participants.…”
Section: Resultsmentioning
confidence: 66%
“…Likewise, there were significant delay effects on SWM for the total scored (F[2.8, 53] = 6.6, p = 0.0006, η 2 = 0.074, after correction with Greenhouse-Geisser epsilon) but not for the maximum obtained (F[3, 57] = 2.1, p = 0.11, η 2 = 0.03).D-amphetamine effect on PLE. As shown in Fig4, wilcoxon signed rank test with continuity correction indicated that there was a significant increase in PLE scores following damphetamine (V = 199, p = 0.00048), relative to placebo (presented in our previous report on funneling illusion[100]). As shown in Table1, d-amphetamine significantly increased scores on the BPRS (V = 129, p = 0.001), MIS (V = 107.5, p = 0.039) and PAS (V = 127, p = 0.017), but not on the Launay-Slade (V = 75, p = 0.16) or SAPS (V = 124.5, p = 0.092) Out of the total of 20 participants, d-amphetamine increased schizotypy scores in 16 participants.PLE and working memory.…”
mentioning
confidence: 52%
“…We recruited 46 participants, more than double the number of participants in previous dexamphetamine studies on BWs. 22,83 Importantly, our previous TFI study involving 20 healthy par ticipants showed that, although dexamphetamine influenced funnelling illusion based on changes in psychometric score, it failed to modify BWs. 83 We manipulated and compared the illusory and psycho logical effects of dexamphetamine at a moderate dose (about 33 mg), which was 2-3 times higher than that used in most previous dexamphetamine challenge studies.…”
Section: E95mentioning
confidence: 96%
“…22,83 Importantly, our previous TFI study involving 20 healthy par ticipants showed that, although dexamphetamine influenced funnelling illusion based on changes in psychometric score, it failed to modify BWs. 83 We manipulated and compared the illusory and psycho logical effects of dexamphetamine at a moderate dose (about 33 mg), which was 2-3 times higher than that used in most previous dexamphetamine challenge studies. We involved participants whose ages and education levels were very close, which provided a homogeneous population and avoided or decreased agerelated cognitive differences.…”
Section: E95mentioning
confidence: 96%